Realizing the value of recycling - Assessing the elements of a policy package - Sun Xi; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
We investigate policies for increasing recycling to facilitate decarbonization within the basic material sector, including market-based policies, such as carbon pricing, advanced disposal fee and minimum recycled content requirement, and non-market policies, such as product design standard. We develop an analytical model to assess the role of these policy instruments for recycling related choices of manufacturing industry, consumers, and waste management. We find that individual policy instruments can deliver some benefits in terms of emission reductions and welfare improvements, but that a package of policy instruments is necessary to reach the welfare maximum and effective scale of emission reductions and resource saving.
Keywords: D62; H23; Q53; Q54; 330; industry decarbonization; market failure; high-quality recycling; policy package